Rural Australian community pharmacists' views on complementary and alternative medicine: a pilot study - Willis Jon A; Dickson-Swift Virginia A; Bushett Nicole J; Wood Pene (BMC, 2011)
Abstract Background Complementary and alternative medicines (CAMs) are being used increasingly across the world. In Australia, community pharmacists are a major supplier of these products but knowledge of the products and interactions with other medicines is poor. Information regarding the use of CAMs by metropolitan pharmacists has been documented by the National Prescribing Service (NPS) in Australia but the views of rural/regional community pharmacists have not been explored. The aim of this pilot study was to explore the knowledge, attitudes and information seeking of a cohort of rural community pharmacists towards CAMs and to compare the findings to the larger NPS study. Methods A cross sectional self-administered postal questionnaire was mailed to all community pharmacists in one rural/regional area of Australia. Using a range of scales, data was collected regarding attitudes, knowledge, information seeking behaviour and demographics. Results Eighty eligible questionnaires were returned. Most pharmacists reported knowing that they should regularly ask consumers if they are using CAMs but many lacked the confidence to do so. Pharmacists surveyed for this study were more knowledgeable in regards to side effects and interactions of CAMs than those in the NPS survey. Over three quarters of pharmacists surveyed reported sourcing CAM information at least several times a month. The most frequently sought information was drug interactions, dose, contraindications and adverse effects. A variety of resources were used to source information, the most popular source was the internet but the most useful resource was CAM text books. Conclusions Pharmacists have varied opinions on the use of CAMs and many lack awareness of or access to good quality CAMs information. Therefore, there is a need to provide pharmacists with opportunities for further education. The data is valuable in assisting interested stakeholders with the development of initiatives to address the gaps in attitudes, knowledge and to improve effectiveness of information seeking behaviour.